THE USE OF ROLE PLAY TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING ABILITY AT GRADE X OF SENIOR HIGH SCHOOL - Isnaini Nuranda (JELLT (Journal of English Language and Language Teaching), 2018)
The purposes of this study are to find out the improvement and the strengths as well as limitation after the use of role play technique in English speaking class for the tenth grade students of SMA PIRI 1 Yogyakarta at X MIA in the academic year of 2017/2018. This study is an Action Research. The data collecting techniques used were observation, interview, and test. The data analysis used was descriptive qualitative. The results indicate that role play promotes the students’ speaking skill development. Through playing the roles, the students were able to answer questions orally, analyze dialogue, speak and express their opinion. The students could also construct dialogues creatively and practice them critically. Therefore, they could reduce their anxiety of feeling afraid and unconfident in speaking. Besides, they also exhibited self-confidence to share their opinion and suggestion during the teaching and learning process.